Exploring Hormonal Pathways and Gene Networks in Crown Root Formation Under Stress Conditions: An Update - Siarhei A. Dabravolski; Stanislav V. Isayenkov (Plants)
Crown root (CR) initiation and development are crucial for the establishment of robust root systems in plants, contributing significantly to stress tolerance and overall growth. This manuscript explores the regulatory roles of key hormones and genes involved in CR formation, with a focus on their interactions under conditions of drought and salt stress. Cytokinins (CK) act as a negative regulator of CR development, while auxin (AUX) serves as a positive driver, facilitating cellular growth and division. Wuschel-related homeobox (WOX) genes, particularly OsWOX11, play a central role by integrating CK and AUX signalling to regulate downstream targets such as OsCRL1 and auxin biosynthetic pathways. Other hormones, including jasmonic acid (JA) and gibberellin (GA), display context-dependent effects, modulating CR initiation based on environmental conditions. Critical genes like OsESG1 and OsFBX257 have been associated with improved drought resilience, interacting with proteins and kinases such as OsGF14b/c and OsCDPK1. Despite progress, significant challenges remain in mapping the full extent of hormonal crosstalk and gene regulation under stress conditions. This manuscript emphasises the need for future studies to incorporate comprehensive multi-omics approaches, expand the exploration of stress-related hormones like abscisic acid (ABA), and leverage advanced gene-editing techniques. Addressing these gaps will enhance our understanding of CR development and contribute to the development of crops with greater resistance to environmental stresses.